Vitamin C Deficiency Causes Cell Type–Specific Epigenetic Reprogramming and Acute Tubular Necrosis in a Mouse Model. Issue 3 (March 2022) - Yu, Zihui; Xu, Ziying; Liang, Yuan; Yin, Pengbin; Shi, Yue; Yu, Jiayi; Hao, Junfeng; Wang, Ting; Ci, Weimin
Significance Statement: Vitamin C levels decline in patients with various kidney diseases, but the role of the vitamin as an epigenetic regulator in the initiation and progression of kidney diseases has not been characterized. Using Gulo −/− mice, which, like humans, entirely depend on dietary vitamin C, we applied single-cell RNA sequencing, whole genome bisulfite sequencing, and methylated RNA immunoprecipitation sequencing to create the first comprehensive renal cell type–specific transcriptional and DNA/RNA methylation profiles. Vitamin C deficiency induced acute tubular necrosis (ATN) and remodeled DNA/RNA epigenetic modifications in a cell type–specific manner. Cisplatin-induced ATN and AKI had similar transcriptional profiles as Gulo −/− mice. An oxidation-resistant vitamin C derivative, APM, can prevent kidney injuries in cisplatin-induced ATN mice. These findings will aid development of vitamin C as an epigenetic therapy for kidney diseases. Visual Abstract: Abstract : Background: Vitamin C deficiency is found in patients with variable kidney diseases. However, the role of vitamin C as an epigenetic regulator in renal homeostasis and pathogenesis remains largely unknown. Methods: We showed that vitamin C deficiency leads to acute tubular necrosis (ATN) using a vitamin C–deficient mouse model ( Gulo knock-out). DNA/RNA epigenetic modifications and injured S3 proximal tubule cells were identified in the vitamin C–deficient kidneys using whole-genome bisulfite sequencing, methylated RNA immunoprecipitation sequencing, and single-cell RNA sequencing. Results: Integrated evidence suggested that epigenetic modifications affected the proximal tubule cells and fenestrated endothelial cells, leading to tubule injury and hypoxia through transcriptional regulation. Strikingly, loss of DNA hydroxymethylation and DNA hypermethylation in vitamin C–deficient kidneys preceded the histologic sign of tubule necrosis, indicating the causality of vitamin C–induced epigenetic modification in ATN. Consistently, prophylactic supplementation of an oxidation-resistant vitamin C derivative, ascorbyl phosphate magnesium, promoted DNA demethylation and prevented the progression of cisplatin-induced ATN. Conclusions: Vitamin C played a critical role in renal homeostasis and pathogenesis in a mouse model, suggesting vitamin supplementation may be an approach to lower the risk of kidney injury.